REPRESENTASI CITRA LAKI-LAKI BUDAYA SUNDA (STUDI ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE DALAM SINETRON PREMAN PENSIUN) - Nanda Utaridah (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
Lifting Sunda culture in this Retired Sinetron Freeman become fascination a look on because of setting, dialectal of Ianguage, and comedy situation in its story jell with atmosphere of kesundaan and town of Bandung. Retired Freeman narrate life of group "small" freeman mastering terminal area, market and merchant of cloister in town of Bandung. The Reality freeman many in men domination, so becoming this research inspiratif for mendeskripsikan and analyse Sunda men image which is construction differen in this sinteron. Research use descriptive approach qualitative with analysis of semiotik model Charles Sanders Peirce. Result of analysis there are ten figure picture player of men in Retired Freeman sinetron which is representasi as cultural men image of Sunda having meaning in life, namely as follows 1) Men Sunda have style fashion in dressing as image identity, 2) Men Sunda have the understanding of Sunda character and ethos namely, "Cageur, Bageur, Bener, Singer, and Pinter,” 3) Men Sunda inculcate life value "Silih Asah, Silih Asuh and Silih Asih" in society and family, and 4) Men Sunda prefer pattern "Riung Mumpulung or Bengkung ngariung bongkok ngaronyok" namely shake together with family and brother in a state of liking and is hard. Men Sunda showing many image which are positive in this Retired Freeman sintron even can argue stereotype they which have expanded in society.